Peran Ayah dalam Pembentukan Karakter Remaja di SMK Hidayah Semarang - Inaya Putri Riswana; Rina Rachmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
In a family, the role of fathers in parenting is an important component for child development. Fathers' involvement in parenting reflects a form of active participation that includes physical, affective, and cognitive aspects. The psychological impact of fathers' involvement is reflected in the ability to regulate emotions, self-esteem, self-confidence, self-control, and social skills of adolescents. Adolescence is a developmental phase characterized by biological, cognitive, and social-emotional changes, so the support of the father's role becomes increasingly important in forming positive character. This research aims to describe the role of fathers in the character formation of adolescents at SMK Hidayah Semarang. This study uses a quantitative approach with a descriptive percentage design. Data were collected through the distribution of questionnaires to grade 10 students at SMK Hidayah Semarang. Data collection was carried out using questionnaires that had been tested for validity and reliability. The results of the reliability test showed a Cronbach's Alpha value of 0.849 which is included in the very reliable category. Data analysis used descriptive percentage techniques to determine the level of fathers' roles in various aspects. The results showed that the role of fathers in the character formation of adolescents is in the high category with a percentage of 62.1%. The highest-scoring aspect was the role of consultant and advisor, while aspects that still need improvement were the role of friend and the provision of affection and attention. Overall, fathers' roles have been effective in supporting adolescent character development, but improvements are still needed, particularly in emotional closeness and communication.